Decision making after 50 days of simulated weightlessness - Lipnicki, Darren M.; Gunga, Hanns-Christian; Belavy, Daniel L.; Felsenberg, Dieter (Brain research, 2009)
By restricting physical activity levels, the bed rest simulation of weightlessness could be associated with changes in prefrontal cortex functioning that manifest as cognitive decrements, particularly for executive cognitive functions. We aimed to determine if performance on an executive function task was indeed affected by bed rest. The Iowa Gambling Task, a card game measuring real-life decision making processes, was administered to 25 healthy males (aged 21–45 years) selected to undergo 60 days of 6° head-down tilt bed rest for the 2nd Berlin BedRest Study (BBR2-2). Testing was conducted either 6 days before beginning bed rest ( n = 13) or on the 51st day of bed rest ( n = 12). The task performance scores of subjects tested before bed rest were not significantly different from those tested during bed rest. However, subjects tested during bed rest failed to adapt their card selection strategy as the Iowa Gambling Task progressed. This was unlike the subjects tested before bed rest, who switched between decks on consecutive card selections less frequently in latter stages of the task. An influence of prolonged bed rest on decision making could have implications for the planning of human spaceflights to Mars, or for any circumstance in which adequate physical activity levels are not achieved.